Ehdotus pysyväksi avustusmekanismiksi journalismin tukemiseksi - Wirén Sini; Aho Hanne; Ala-Fossi Marko; Grönlund Mikko; Holmberg Jukka; Korpisaari Päivi; Villi Mikko; Virta Päivi-Maria; Asp Emil; Nykänen Emmi; Andersson Atro (Liikenne- ja viestintäministeriö, 2022)
On 25 June 2020, the Ministry of Transport and Communications appointed a working group with representatives of the media sector and experts in the field to assist in the further preparation of a temporary government grant in support of journalism and to reflect on a permanent aid mechanism for this purpose. The working group also discussed the feasibility of public support for media that produce multilingual and multicultural journalism. Members of the working group: Hanne Aho, Chair, Union of Journalists in Finland; Marko Ala-Fossi, Media Researcher, University of Tampere; Mikko Grönlund, Research Manager, University of Turku; Jukka Holmberg, CEO, Finnish Media Federation; Mikko Villi, Professor, University of Jyväskylä; and Päivi Korpisaari, Professor in Communication Law, University of Helsinki. The working group proposes editorial production support as the main form of assistance. Another proposed form of assistance is development support that could be granted not only to newly established media companies but also for development projects of an established media company. Both forms of assistance are intended to support media that provide news and current affairs content. The working group also proposes specific support for community media. The proposed model would promote reliable, multi-faceted and socially significant communication as a whole.